Trade linkages and domestic market concentration: an empirical exploration for Malaysia - Evelyn S. Devadason; Thirunaukarasu Subramaniam (Penerbit Universiti Kebangsaan Malaysia, 2014)
This paper examines the univariate relationship between global linkages of the Malaysian manufacturing sector in the form of export intensity and intra-industry trade, respectively, on inter-industry concentration. The recently developed fully modified ordinary least squares (FMOLS) and dynamic ordinary least squares (DOLS) panel cointegration techniques are employed. The estimated long-run coefficients reveal that intra-industry trade contributes towards more concentrated markets. However, export intensity is not significantly associated with market dominance. This suggests that domestic market structure is directly related to industries that engage in two-way trade flows or trade overlap. The structure of trade therefore deserves further attention when analyzing market dominance in the Malaysian manufacturing sector, which is globally integrated at the production level. It would thus be viable to examine why and to what extent vertically integrated industries that simultaneously facilitate not just external markets for components or final products but also the import markets for components (inputs) pose barriers to industries that are less networked globally.